2016
DOI: 10.1242/jeb.134924
|View full text |Cite
|
Sign up to set email alerts
|

Sperm chemotaxis promotes individual fertilization success in sea urchins

Abstract: Reproductive success fundamentally shapes an organism's ecology and evolution, and gamete traits mediate fertilization, which is a critical juncture in reproduction. Individual male fertilization success is dependent on the ability of sperm from one male to outcompete the sperm of other males when searching for a conspecific egg. Sperm chemotaxis, the ability of sperm to navigate towards eggs using chemical signals, has been studied for over a century, but such studies have long assumed that this phenomenon im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…We propose that when sperm is absent, P. acuta produces parthenogenic offspring through automixis, diploidization of oocytes, or restitutional meiosis (Figure 1); alternately, when sperm is present, P. acuta is able to reproduce sexually (Figure 3) -a strategy consistent with the reproductive assurance hypothesis. Indeed, eggs of some coral species contain sperm attractant molecules, and this could explain why sexual reproduction is favored in the presence of sperm (Coll et al, 1994;Hussain et al, 2016). Our hypothesis would explain why Combosch and Vollmer (2013) observed a greater proportion of sexually produced larvae at the beginning of the planulation event -colonies were isolated the day prior to planulation, and thus eggs may have already been fertilized by other colonies in the aquaria.…”
Section: Observations and Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We propose that when sperm is absent, P. acuta produces parthenogenic offspring through automixis, diploidization of oocytes, or restitutional meiosis (Figure 1); alternately, when sperm is present, P. acuta is able to reproduce sexually (Figure 3) -a strategy consistent with the reproductive assurance hypothesis. Indeed, eggs of some coral species contain sperm attractant molecules, and this could explain why sexual reproduction is favored in the presence of sperm (Coll et al, 1994;Hussain et al, 2016). Our hypothesis would explain why Combosch and Vollmer (2013) observed a greater proportion of sexually produced larvae at the beginning of the planulation event -colonies were isolated the day prior to planulation, and thus eggs may have already been fertilized by other colonies in the aquaria.…”
Section: Observations and Discussionmentioning
confidence: 81%
“…In low population densities, a mixed-mode of reproduction would be expected to reinforce the benefits of the strategy: reproductive success would still be possible, thus allowing the species to colonize new habitats or rebound from catastrophic events even in the absence of conspecifics (Tsounis and Edmunds, 2016). However, when mates are within the sperm dispersal range, P. acuta may potentially use chemical cues such as sperm chemotaxis to attract non-self sperm (Coll et al, 1994;Hussain et al, 2016), and may thus benefit from the advantages of sexual reproduction. The modular nature of corals may also allow for multiple paternity per colony: when in close proximity to multiple mates, each polyp in a colony may be fertilized by a different father.…”
Section: Observations and Discussionmentioning
confidence: 99%
“…Using a microfluidic chemotaxis sorter coupled with IVF, Hussain et al recently showed that chemotactic sperms subsequently increased the fertility rate in sea urchin . Zhang et al devised a hexagonal shape microchamber connected to six microchannels to simultaneously study the effect of sperm chemotaxis at three concentration gradients of progesterone .…”
Section: Continuous‐flow Microfluidics In Artmentioning
confidence: 99%
“…Chemotaxis is one of the most important factors in sperm guidance during fertilization among marine invertebrates, which provides a good inspiration to study the fertilization of human (De Lisa et al, 2013; Hussain et al, 2016). The sperm-attracting substances secreted by female genital tract are called chemoattractant.…”
Section: Introductionmentioning
confidence: 99%